Cardiovascular and renal burdens among patients with MAFLD and NAFLD in China - Wang, Yuying; Yu, Yuetian; Zhang, Haojie; Chen, Chi; Wan, Heng; Chen, Yi; Xia, Fangzhen; Yu, Shiyan; Wang, Ningjian; Ye, Lin; Lu, Yingli (Frontiers in Endocrinology, 2022)
Background/Purpose Metabolic associated fatty liver disease (MAFLD) was proposed as a new definition to put emphasis on the metabolic aspects of nonalcoholic fatty liver disease (NAFLD). We aim to compare the cardiovascular and renal burden between MAFLD and NAFLD patients. Methods 12183 participants were enrolled in East China. The cardiovascular burden (Framingham risk score and previous cardiovascular diseases (CVD)) and renal burden (eGFR and chronic kidney disease (CKD)) were measured. Results The risk of hypertension, dyslipidemia, diabetes, overweight/obesity, and central obesity of MAFLD patients were higher than those of NAFLD. Patients with MAFLD have a similar or higher beta coefficients in Framingham risk score [beta(95%CI): male 0.062(0.055,0.069)vs0.041(0.033,0.048); female 0.014(0.012,0.016)vs0.012(0.01,0.014)], and higher odds ratio in previous CVD [odds ratio(95%CI): male 1.50(1.22,1.85)vs1.35(1.1,1.66); female 1.58(1.33,1.87)vs1.45(1.22,1.72)], compared with those with NAFLD. However, compared with males with MAFLD, the odds ratio of CKD was higher in those with NAFLD [eGFR: -2.731(-3.422, -2.041) vs-3.578(-4.268, -2.887). CKD: 1.44(1.05,1.96) vs1.56(1.14,2.12)]. In female, CKD was only marginally associated with NAFLD [0.8(0.62,1.02), P=0.075], but not MAFLD [0.87(0.68,1.11), P=0.268]. Conclusions Patients with MAFLD have a similar or higher risk of future and previous CVD compared with those with NAFLD, but the risk of CKD was higher in male with NAFLD.